Age- and sex-related variations of normal spleen T1rho and the more stable liver T1rho to spleen T1rho ratio - Wáng, Yì Xiáng J.; Yu, Wei-Ling; Deng, Min (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
We aim to evaluate the potential age- and sex-related variations of normative values of spleen T1rho.Two T1rho sequences were used, with one based on fast spin echo sequence (FSE) and the other based on gradient echo sequence (GRE). Spleen and liver FSE T1rho values were measured in 52 healthy volunteers (36 females, 16 males), and spleen and liver GRE T1rho values were measured in 14 healthy volunteers (6 females, 8 males).For FSE data, an age-related decreasing trend of spleen T1rho was noted for both females and males. This trend was consistent with female liver T1rho values, while such a trend was not noted for male liver T1rho. Females had a higher T1rho than males, both for the spleen (92.8 vs 77.3 ms, p<0.0001) and for the liver (44.2 vs. 38.9 ms, p<0.0001, FSE data). The spleen T1rho value was approximately double the liver T1rho value. The spleen T1rho and liver T1rho were positively correlated, both for FSE data (r=0.611) and GRE data (r=0.541). When the spleen T1rho was used to normalize the liver T1rho, the ratio of T1rholiver/T1rhospleen largely removed the sex and age effect. The spleen T1rho in menstrual phase women was 10.7% lower (p=0.012) than that of non-menstrual phase women, while the liver T1rho in menstrual phase women was 3.8% lower than that of non-menstrual phase women.Since women in the menstrual phase tend to have lower body iron, the fact that both liver T1rho and spleen T1rho are shorter among women in the menstrual phase than women in the non-menstrual phase indicates that liver and spleen T1rho physiological variations may not be dominantly affected by the iron content of the tissue. If a pathology has only affected the liver while the spleen is normal, there is a possibility the ratio T1rholiver/T1rhospleen may offer better characterization of liver pathologies.
Keywords: liver; spleen; magnetic resonance imaging; T1rho; aging; menstrual cycle